AI for Cancer Detection: Accuracy and Real-World Results in Digital Health - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
AI for Cancer Detection: Accuracy and Real-World Results in Digital Health The integration of Artificial Intelligence (AI) into medical diagnostics, par...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care